2020
DOI: 10.1088/1755-1315/564/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators of metals pollution in the coastal sediments in Sangihe Islands Regency, North Sulawesi Province, Indonesia

Abstract: Metal pollution in coastal areas is one of the focused environmental concerns. Sediment quality in the coastal zone reflects the long-term environmental status because it keeps a record of the development in the area. Quality indicators for metals in surface sediments were evaluated at 18 points of sediment sampling sites of these three bays using the Enrichment factor (EF) and the geo accumulation index (Igeo). Research locations in the coastal areas of Sangihe Island, Talengan Bay, Manalu, and Dagho Bay have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Twenty-six papers from Indonesia were not included in the calculations of ERI and HHRA [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ]. The exclusions were mainly due to not all the three metals (Cu, Pb, and Zn) being analyzed and reported in these papers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six papers from Indonesia were not included in the calculations of ERI and HHRA [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ]. The exclusions were mainly due to not all the three metals (Cu, Pb, and Zn) being analyzed and reported in these papers.…”
Section: Resultsmentioning
confidence: 99%
“…Armid et al [ 186 ] studied HM pollution in the surface sediments of Kendari Bay (Southeast Sulawesi), suggesting that the Kendari Bay surface sediment was regarded as an unpolluted area by HMs such as Cu and Zn). According to Asaf et al [ 187 ], the metal concentration in the coastal sections of Sangihe Island (Talengan Bay, Manalu, and Dagho Bay; North Sulawesi) was below the background value. Cu, Pb, and Zn levels in Makassar’s coastal water showed that it was still unpolluted, according to Bohari and Palutturi [ 188 ].…”
Section: Resultsmentioning
confidence: 99%